Partnering to Reduce Colon Cancer Health Disparities Among the American Indian Population in Michigan - Noel Pingatore; Angela Lewis Precht; Georgetta Alverson; Glenn Copeland; Betty Jahnke; Andrea Dwyer; Robey B. Champine (Journal of Community Engagement and Scholarship, 2022)
American Indian and Alaska Native people experience higher rates of several cancers, including lung, colorectal, liver, stomach, and kidney cancers, compared to non-Hispanic White people in the United States. Cancer disparities are also prominent among the American Indian population and vary by region. Disproportionately high rates of colon cancer were identified among three tribal communities in Michigan by linking each tribe’s enrollment roster to the state cancer registry. In response, in 2015 the Inter-Tribal Council of Michigan received funding from the Office of Minority Health within the U.S. Department of Health and Human Services to work with the three tribes to develop and implement the Tribal Colon Cancer Collaborative Project. The project used a community-based participatory research approach and a learning collaborative model to implement a multipronged initiative intended to improve colon cancer screening rates and outcomes among the three tribal communities. Local tribal coordinators were trained in the use of evidence-based interventions, including patient navigation and quality improvement processes, and implemented activities within their respective tribal health settings. Preliminary findings indicated increased colon cancer screening rates and improved rates of early stage cancer diagnoses. This paper describes the processes involved in implementing the project in collaboration with local tribal coordinators and the details of their journey toward improved colon cancer health outcomes.